The Shadow of Stigma: The Black’s Outrage in the Play Hang and their Journey toward Achieving Self-Awareness - Kadhim, Nabaa Jawad (Tasnim International Journal for Human, Social and Legal Sciences, 2026)
For thousands of years, racism has been a significant contributor to numerous civil and global conflicts, as well as a source of various societal issues such as bullying, discrimination, and humiliation. Its repercussions persist to this day. Black communities have historically been among the most adversely affected by racism. Consequently, the phenomenon known as "Black Rage" has emerged to mitigate racial discrimination faced by these communities. This movement has played a vital role in enhancing the self-awareness of Black individuals, like in the play Hang by Debbie Tucker Green. She offers a transnational and transhistorical perspective on these issues through wrath as a tool for reflection on racism and the administration of criminal justice and empowering the black people to realize their aspirations and objectives and to assert their legitimate rights.